Service Quality and Customer Satisfaction in Islamic Banking - Nur Syuhanida, Samsuddin (2011)
Service quality is a gap between perceptions toward service provided. Customer satisfaction is response by emotion or attitude of customer after use the services and products. Today, researcher wants to identify the level of service quality in Islamic banking at Perak state whether low or high. Researcher also wants to identify the level of customer satisfaction towards products and services provided by Islamic banking. Objectives of this research are to determine customer satisfaction level towards the services provides by Islamic banking, to assess customer perception towards service quality level which is provide by Islamic banking, to determine service quality level in Islamic banking and to identify differential between demographic factor and customer satisfaction. Researcher use quantitative data in order to collect the data and get the result.